UNCOVERING KEY DRIVERS OF RISING DENGUE CASES IN MALAYSIA: A SYSTEMATIC REVIEW - Muniandy, Kalaivani; Rahmat Dapari; A. Alabed, Alabed Ali; Yudhastuti, Ririh; Suwanmanee, San (Malaysian Journal of Public Health Medicine, 2026)
Dengue fever, a viral disease transmitted by Aedes mosquitoes, continues to escalate as a significant public health threat in Malaysia, leading to a growing burden on the healthcare system and the economy. Despite the increasing incidence, the factors contributing to the rise in dengue infections remain multifaceted and under-explored within the Malaysian context. Addressing these factors is crucial for devising more effective preventive strategies and interventions. This study provides a comprehensive examination of the complex factors driving the surge in dengue cases in Malaysia. By systematically analysing human behaviours, environmental conditions, vector dynamics, and the viral characteristics, the study aims to uncover the underlying determinants and inform targeted public health responses. A systematic review was conducted, incorporating studies published between 2011 and 2024, selected through a rigorous screening process from databases including ScienceDirect and EBSCOhost. The review adhered to the PRISMA guidelines, with quality assessments performed using the Mixed Method Appraisal Tool (MMAT) for the included 20 studies. These studies were analyzed to synthesize evidence on the key drivers for rise of dengue transmission in Malaysia. A total of 20 studies were included in this systematic review and the results were categorized into four core domains: human factors, environmental influences, vector dynamics, and virus characteristics. Human factors such as age, occupation, and socioeconomic conditions were identified as significant determinants, with older adults and those in high-risk occupations exhibiting increased vulnerability to severe dengue. Environmental conditions, particularly rapid urbanization, poor waste management, and dense population clusters, emerged as critical factors fostering mosquito breeding and transmission. The coexistence of Aedes aegypti and Aedes albopictus in both urban and rural settings exacerbated the risk. Virus-related findings revealed that DENV-3 was the dominant serotype linked to higher disease severity, while mixed serotype infections significantly heightened the risk of severe outcomes, underlining the role of viral factors in the progression of the disease. Overall, urbanisation, population density, and socioeconomic disparities were consistently identified as key drivers across the included studies. The rising incidence of dengue infections in Malaysia can no longer be attributed to a single cause but rather to an intricate interaction of human, environmental, vector, and viral factors. This study provides compelling evidence that addressing these determinants through integrated public health strategies, spanning urban planning, vector control, socioeconomic reforms, and education is essential to combat the dengue crisis. By focusing on high-risk groups, urban infrastructure, and timely medical interventions, Malaysia can better mitigate future outbreaks and safeguard its population. These findings highlight important implications for public health policy, particularly the need for integrated, multi-sectoral strategies involving urban planning, vector control, socioeconomic interventions, and community engagement. More specific actions, including strengthening surveillance systems and improving urban waste management, are essential to effectively mitigate future outbreaks.